Selective expression of CSPG receptors PTPσ and LAR in poorly regenerating reticulospinal neurons of lamprey. Issue 9 (15th June 2014) - Zhang, Guixin; Hu, Jianli; Li, Shuxin; Huang, Lisa; Selzer, Michael E.
ABSTRACT Disability following spinal cord injury is due to failure of axon regeneration, which has been ascribed to environmental factors in the central nervous system and a developmental loss of intrinsic growth capacity in neurons. Recently, the receptor‐like protein tyrosine phosphatases, protein tyrosine phosphatase σ (PTPσ) and leukocyte common antigen‐related phosphatase (LAR), have been identified as specific receptors for the regeneration‐inhibiting matrix molecules chondroitin sulfate proteoglycans (CSPGs). After spinal cord transection in lampreys, axons of the large, identified reticulospinal neurons have heterogeneous regenerative abilities. The bad‐regenerating neurons also undergo a delayed form of axotomy‐induced apoptosis. In the present study, a lamprey genomic database was used to identify homologs of CSPGs, clone PTPσ and LAR, and examine their mRNA expression. CSPG immunoreactivity was increased significantly near the lesion at 2 weeks post transection, and decreased thereafter. Both receptors were expressed selectively in the bad‐regenerating neurons and had overlapping cellular distributions. PTPσ was upregulated with age (LAR was not evaluated). By 2 weeks post transection, neurons expressing PTPσ also showed caspase activation, suggesting apoptosis. The probability of axon regeneration for individual identified neurons was negatively correlated with the expression level of PTPσ in both control and spinal cord–transected lampreys. In an animal 7 weeks post transection, regenerated axons were labeled retrogradely from beyond the transection. PTPσ expression and caspase labeling was seen only in neurons whose axon had not regenerated. These results are consistent with a possible role for PTPσ (and LAR) in both retrograde neuronal death and the poor intrinsic regenerative ability of bad‐regenerating neurons. J. Comp. Neurol. 522:2209–2229, 2014. © 2013 Wiley Periodicals, Inc.